Prevalence of Chlamydia trachomatis among subfertile couples of LPPKN subfertility clinic - Nekmat, Nily Waheeda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Chlamydia trachomatis is the most prevalent sexually transmitted infection world wide caused by the bacterial agent named Chlamydia trachomatis. Long term chlamydial infection has a negative impact on the female reproductive system and often leads to infertility. We determined the prevalence of Chlamydia trachomatis and its associated factors among subfertile couples attending the Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN) Subfertility Clinic. Method: Blood samples were collected from 95 couples (190 respondents) for Chlamydia trachomatis IgG antibody testing. The Enzyme-Linked Immunosorbent Assay (ELISA) technique was used to detect outer membrane protein complexes of Chlamydia trachomatis in the assay. Results: Chlamydia trachomatis IgG antibody seropositivity was detected in 14 husbands (14.7%) and 17 wives (17.9%). The prevalence of Chlamydia trachomatis among these couples was 22.1%. Our findings found no significant association between Chlamydia trachomatis and its associated factors, but the prevalence rate among the studied population is of concern. Conclusion: The screening of Chlamydia trachomatis among couples is recommended for integration in the subfertility investigation procedure. It is crucial, particularly for women with tubal factor infertility (TFI).